The Effectiveness of Electrical Stimulation For Bell's Palsy Patients: Literature Review - Az Zahra, Fitria; Subagia, Rillo Tri; Alpiah, Dini Nur (Worldwide Research Publishing, 2024)
Many problems can occur in Bells Palsy, one of which is weakness in facial muscles. prevalence of Bell's palsy around 19.55% number of cases in Indonesia. This study aims to determine effectiveness of electrical stimulation in facial muscle strength in Bell's Palsy. This literature review research uses PICO as a database. Experimental group received sessions of transcutaneous electrical stimulation over period time, while control group received no additional stimulation. Have 4 journals that met criteria and showed results with p-value<0.05. conclusion of journal that receiv. The conclusion this journal is electrical stimulation experienced a significant increase in the strength of their facial muscles compared to control group. Subjective measurements supported improvements in facial expression and speaking ability. We conclude that electrical stimulation can be an effective method for increasing facial muscle strength in people with Bell's Palsy. However, further research’s needed to validate these findings and determine optimal stimulation parameters